Measurement of the inclusive isolated-photon production cross section in pp and Pb–Pb collisions at √ˢɴɴ=5.02 TeV - Zurlo, N.; Zugravel, S.C.; Zhu, Y.; Zhu, S.; Zhu, J.; Zhou, Y.; Zhou, D.; Zhi, Y.; Zherebchevsky, V.; Zhao, M.; Zhang, Z.; Zhang, Y.; et al. (Springer Nature, 2025)
The ALICE Collaboration at the CERN LHC has measured the inclusive production cross section of isolated photons at midrapidity as a function of the photon transverse momentum ( Pʸᴛ ), in Pb–Pb collisions in different centrality intervals, and in pp collisions, at centre-of-momentum energy per nucleon pair of √ˢɴɴ = 5.02 TeV. The photon transverse momentum range is between 10–14 and 40–140 GeV/c , depending on the collision system and on the Pb–Pb centrality class. The result extends to lower Pʸᴛ than previously published results by the ATLAS and CMS experiments at the same collision energy. The covered pseudorapidity range is |ηʸ| < 0.67 . The isolation selection is based on a charged particle isolation momentum threshold Pⁱˢᵒ′ᶜʰᴛ = 1.5 GeV/c within a cone of radii R = 0.2 and 0.4. The nuclear modification factor is calculated and found to be consistent with unity in all centrality classes, and also consistent with the HG-PYTHIA model, which describes the event selection and geometry biases that affect the centrality determination in peripheral Pb–Pb collisions. The measurement is compared to next-to-leading order perturbative QCD calculations and to the measurements of isolated photons and Z⁰ bosons from the CMS experiment, which are all found to be in agreement.
Keywords: Physics; Production (economics); Cross section (physics); Photon; Section (typography); Particle physics; Nuclear physics; Optics; Quantum mechanics; Economics; Computer science; https://purl.org/pe-repo/ocde/ford#1.03.00